Association between aircraft, road and railway traffic noise and depression in a large case-control study based on secondary data - Seidler, Andreas; Hegewald, Janice; Seidler, Anna Lene; Schubert, Melanie; Wagner, Mandy; Dröge, Patrik; Haufe, Eva; Schmitt, Jochen; Swart, Enno; Zeeb, Hajo (Environmental research, 2017)
Few studies have examined the relationship between traffic noise and depression providing inconclusive results. This large case-control study is the first to assess and directly compare depression risks by aircraft, road traffic and railway noise. The study population included individuals aged ≥40 years that were insured by three large statutory health insurance funds and were living in the region of Frankfurt international airport. Address-specific exposure to aircraft, road and railway traffic noise in 2005 was estimated. Based on insurance claims and prescription data, 77,295 cases with a new clinical depression diagnosis between 2006 and 2010 were compared with 578,246 control subjects. For road traffic noise, a linear exposure-risk relationship was found with an odds ratio (OR) of 1.17 (95% CI=1.10–1.25) for 24-h continuous sound levels ≥70dB. For aircraft noise, the risk estimates reached a maximum OR of 1.23 (95% CI=1.19–1.28) at 50–55dB and decreased at higher exposure categories. For railway noise, risk estimates peaked at 60–65dB (OR=1.15, 95% CI=1.08–1.22). The highest OR of 1.42 (95% CI=1.33–1.52) was found for a combined exposure to noise above 50dB from all three sources. This study indicates that traffic noise exposure might lead to depression. As a potential explanation for the decreasing risks at high traffic noise levels, vulnerable people might actively cope with noise (e.g. insulate or move away).